(3HdZI Gdabjgs - (3GdfLaj, GdWHGWHGFj, eMeO Hf eMeO Jbj Hf QVG, J (B1326(3g` (B1908(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg LGYd GdYde MjGI GdbdhH ef GdQOi (B... (3eSCdI deG Naj GdaQb Ydi cKjQ Hjf GdMb hGdMce hGdJHS GdCeQ HjfgeG eY GHJfGA cKjQ ef GdaQhY GdabgjI YdjgeG hGdaQb aj GdMbhbs
(3BNQgG (B:s
(3BNQgG(B: (3cPdc bHd bhdg hgj bGYOI CNQi eYJHQI HGdfU hGdGLeGY hHGdLedI aEf (B.. (3GLeGY Ydi JCSjS gPg GdbGYOI hEdG adG Odjd YdjgG HfMh GdcdjI hGddg GdYGde HMbGFb CMcGegs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 76s
(3GdPQjYI, L (B3: 81s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis